Kinetic parameters of the intrinsic reactivity of woody biomass and coal chars via thermogravimetric analysis. (15th December 2017) - Al-Qayim, Khalidah; Nimmo, William; Hughes, Kevin; Pourkashanian, Mohammed
Highlights: Intrinsic reactivity of wood pellets and Vietnamese coal chars are reported for the first time in the literature. Higher pyrolysis temperatures produce chars with higher reactivity. Biomass char has higher intrinsic reactivity than the coal char in T > 973 K. Ash content of Vietnamese coal plays a negative role in pyrolysis, but a positive role in the char combustion. A new correlation of the char surface area and density with the fuel properties and temperature. Abstract: The available data on intrinsic kinetic parameters of wood char combustion is limited in the literature. The intrinsic reactivity of porous char particles reflects the variance in the pore structure resulted from various compositions of parent biomass or coal fuels. In this study detailed kinetic models for calculating the intrinsic reaction rate and the Arrhenius parameters in two combustion zones are developed for the char combustion. The influence of the parent fuel composition and the thermal treatment on the char oxidative reactivity observed on the char surface area and particle density are explored through a mathematical model of the char service area and density. A higher reactivity of the wood pellets than coal and enhanced reactivity with the increasing pyrolysis temperature were observed as well.